2015
DOI: 10.1371/journal.pone.0120004
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Service Use by Young People: The Role of Caregiver Characteristics

Abstract: AimsMany children and adolescents experiencing mental health problems do not receive appropriate care. Strategies to encourage appropriate access to services might be improved by a more detailed understanding of service use determinants within this group. In view of caregivers’ key role in young people’s pathways to care, this study aimed to advance understanding of caregiver-related characteristics that influence service use among young people.MethodsWe interviewed 407 primary caregivers of young people aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 53 publications
4
52
0
Order By: Relevance
“…One possible interpretation of this finding is that many parents may feel they would benefit from some support, but this is not enough to prompt actual help-seeking behaviour; or it may relate to a belief that seeking professional help for a child's anxiety may facilitate access to direct support for a child rather than for a parent. In line with previous studies, our findings also indicate that parents' own mental health plays a role in help-seeking for child anxiety [14,15], but we found that it was parents' prior use of mental health services, not their mental health symptoms, that was uniquely associated with help-seeking for a child. We did not find evidence that parents' perceptions surrounding the helpfulness of their mental health support was associated with help-seeking for their child, but it is possible this is a reflection of the limited variability in perceived helpfulness reported in this sample.…”
Section: Main Findingssupporting
confidence: 92%
See 2 more Smart Citations
“…One possible interpretation of this finding is that many parents may feel they would benefit from some support, but this is not enough to prompt actual help-seeking behaviour; or it may relate to a belief that seeking professional help for a child's anxiety may facilitate access to direct support for a child rather than for a parent. In line with previous studies, our findings also indicate that parents' own mental health plays a role in help-seeking for child anxiety [14,15], but we found that it was parents' prior use of mental health services, not their mental health symptoms, that was uniquely associated with help-seeking for a child. We did not find evidence that parents' perceptions surrounding the helpfulness of their mental health support was associated with help-seeking for their child, but it is possible this is a reflection of the limited variability in perceived helpfulness reported in this sample.…”
Section: Main Findingssupporting
confidence: 92%
“…Parents were asked if they had spoken to a professional about their own mental health using an item sourced from similar surveys [15,32]. Where applicable, parents also indicated the professional they had spoken to and rated the helpfulness of the support they received (not at all helpful = 0 to extremely helpful = 4).…”
Section: Parent Mental Health Service Usementioning
confidence: 99%
See 1 more Smart Citation
“…Further, purposive sampling was used to achieve a balanced sample amongst those who met inclusion criteria in terms of the following individual and family-characteristics: gender, age, ethnicity, and caregivers' reports of stigma. Data on the first three characteristics were collected during the initial screening assessment (2005)(2006)(2007)(2008)(2009)(2010), and data on caregivers' intended stigmatizing behaviors were collected using the Reported and Intended Behaviour Scale (Evans-Lacko et al, 2011) during subsequent data collection (2011)(2012) (Gronholm et al, 2015).…”
Section: Recruitment and Samplingmentioning
confidence: 99%
“…Moreover, access to mental health care for adolescents is often impeded by the design of the relevant health system (e.g. CAP specialists are working primarily in a consulting function, or treat only severely mentally ill patients) [1,18,59]. However, early identification (when combined with effective treatment) is one of the main predictors of functional outcome and social adaptation in many patients with mental health disorders [12,51].…”
Section: Introductionmentioning
confidence: 99%